Return on Brand Investment – Taking a Data-driven Approach to Branding - Roman Reichelt; Minh Dang Nguyen; Stephanie Trachsel; Anna Benner (Marketing Review St.Gallen, 2023)
The Credit Suisse 2022 brand refresh took a data-driven approach, combining classic inside-out analysis with customer and brand research and adding layers of implicit and predictive testing using the latest technologies. The new brand positioning and design drove KPIs and generated a positive return on brand investment, proving that brands can drive business.
Keywords: 650